2019
DOI: 10.1039/c9nr02566a
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of a robust hydrogen-bonded octylphosphonate network on cesium lead bromide perovskite nanocrystals for light-emitting diodes

Abstract: Ligand exchange with octylphosphonate enhances PLQY and LED efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 37 publications
2
82
0
Order By: Relevance
“…9.5 ppm and 11 ppm that should correspond to acid protons. 44 The narrowing of the 31 P peak at 26 ppm could arise because a singly deprotonated phosphonic acid may coordinate to the surface in a monodentate fashion, permitting rotation that could help to average inhomogeneous broadening. The presence of two acid 1 H NMR signals suggest that there are distinct binding sites on the surface for the monoanionic 10-undecenylphosphonate.…”
Section: Resultsmentioning
confidence: 99%
“…9.5 ppm and 11 ppm that should correspond to acid protons. 44 The narrowing of the 31 P peak at 26 ppm could arise because a singly deprotonated phosphonic acid may coordinate to the surface in a monodentate fashion, permitting rotation that could help to average inhomogeneous broadening. The presence of two acid 1 H NMR signals suggest that there are distinct binding sites on the surface for the monoanionic 10-undecenylphosphonate.…”
Section: Resultsmentioning
confidence: 99%
“…Typically, short esters have been most successful. Depending on the ligand system employed, butyl acetate, [44] ethyl acetate, [35,41,43,[71][72][73][74][75][76][77] mixtures of ethyl and methyl acetate, [78,79] and methyl acetate alone, [67,[80][81][82][83] have been employed. Figure 6 shows a screening study of 36 potential antisolvents, it concurred on the efficacy of short esters, but indicated that diethylene glycol dimethyl ether (diglyme) was the most effective.…”
Section: Antisolvent Purificationmentioning
confidence: 99%
“…[80] This remarkable stability toward antisolvent washing was later attributed to the interligand hydrogen bonding between adjacent octylphosphonate ligands. [73] Figure 5. "Triple-ligand" surface passivation approach for CsPbBr 3 nanocrystals: a) The precursors and synthesis protocol, b) TEM image, c) HRTEM image, d) the three ligands employed, TOAB acts only as a solvation agent while DDAB and OTAc coordinate to the NC surface, e) photograph of the purified NC ink, f) time-resolved photoluminescence data, and g) current density against voltage plot for LEDs fabricated from NCs with either oleic acid or octanoic acid ligands.…”
Section: Antisolvent Purificationmentioning
confidence: 99%
See 2 more Smart Citations